Legal Protection in App-Based Transportation Partnerships and Consumers in Indonesia - Desril, Raja; Santoso, Mulia Akbar (Kosmik Hukum, 2026)
The app-based transportation sector, such as Gojek and Grab, has rapidly developed in Indonesia, yet it still faces significant challenges regarding the legal regulations governing the partnership between platform providers and driver partners. The lack of clear legal norms has led to uncertainty regarding the rights and obligations of both parties, which ultimately reduces legal protection for both drivers and consumers. This study aims to analyze how Indonesia's legal system regulates this partnership and evaluate the extent to which existing regulations provide adequate protection for drivers and consumers. The main research questions address how Indonesia's legal system governs partnerships in this sector and to what extent the regulations support the principle of justice. The research method used is normative legal research, employing legislative, conceptual, and theoretical approaches. The findings show that Indonesia's legal system has not provided sufficient legal certainty in these partnerships. Protection for both drivers and consumers remain limited, particularly regarding labor rights and dispute resolution mechanisms. This study suggests the need for clearer and more detailed regulatory reforms to create a more equitable and transparent relationship between companies, drivers, and consumers.